Bosnia and Herzegovina : Technical Assistance Report-Implementation of a New Reserve Requirement Framework. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2019)
This Technical Assistance (TA) report on Bosnia and Herzegovina highlights that the negative spread in a context of structural lower returns on foreign exchange reserves and sizable capital inflows has led to a gradual and steady erosion of the currency board coverage ratio. The Central Bank of Bosnia and Herzegovina (CBBH) requested Technical Assistance to review its reserve requirement framework. The mission recommends aligning the remuneration of reserve requirements on foreign exchange liabilities to the CBBH's opportunity cost. The mission also recommends prescribing the fulfilment in foreign currency of the reserve requirements for foreign currency liabilities. It also suggested altering the remuneration scheme of domestic reserve requirements. In order to be neutral from an intermediation perspective, the reserve requirement remuneration should be aligned to the market-neutral uncovered interest rate parity rate, whereas the remuneration of excess reserves may take place significantly below the market-neutral rate but at or above the foreign currency remuneration rate. The CBBH may benefit from a constructive dialogue with the Area Department or TA to set the new rates of remuneration of domestic reserve requirement and excess reserves.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet